(untitled) (Iraqi Journal of Medical Sciences, 2017)
This is a case report of a patient who achieved a successful vaginal birth for five times attended by a traditional birth attendant twice after two cesarean sections and thrice after three cesarean sections. Keywords: Vaginal birth after cesarean delivery, VBAC, VBAC delivery, trial of labor after cesarean delivery, prior cesarean delivery, risks for uterine rupture, vaginal delivery Citation: Yosra T. Jarjees. Successful trial of labor after primary and repeated cesarean sections: A case report. Iraqi JMS. 2017; Vol. 15(1): 119-121. doi: 10.22578/IJMS.15.1.13